2011
DOI: 10.1097/iae.0b013e318206cb43
|View full text |Cite
|
Sign up to set email alerts
|

Aging Changes of Vitreomacular Interface

Abstract: Spectral-domain optical coherence tomography confirmed the presence of the pocket in all ages. Thickened vitreous cortex and perifoveal posterior vitreous detachment were physiologic findings in older individuals. The lamellar structure of the vitreous cortex may be related to the vitreoschisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…No PVDs were seen in subjects younger than 38 years (all stage 0). As we reported elsewhere, 14 the posterior wall of the PPVP is a very thin vitreous cortex in younger subjects, and it thickens with age. The thickened cortex often has a laminated structure in the perimacula.…”
Section: Discussionmentioning
confidence: 65%
“…No PVDs were seen in subjects younger than 38 years (all stage 0). As we reported elsewhere, 14 the posterior wall of the PPVP is a very thin vitreous cortex in younger subjects, and it thickens with age. The thickened cortex often has a laminated structure in the perimacula.…”
Section: Discussionmentioning
confidence: 65%
“…Aggregation (syneresis) is a consequence of changes in the chemical or conformational state of HA and its interaction with collagen. These alterations lead to increased fibril concentration in the residual gel, associated with a decreased concentration and ultimate absence of fibrils in adjacent areas resulting in liquefaction [33,34]. As liquefaction appears in the central vitreous and overlying the macula, incident light weakens collagen through the production of free radicals [35,36,37,38], and modifies the concentrations in glycosaminoglycans and chondroitin sulfate [39].…”
Section: Biochemistry and Physiology Of The Vitreousmentioning
confidence: 99%
“…This all is confusing in light of how Eisner stated that the Cloquet canal did not exist in the first place. Itakura, Kishi and associates [17][18][19] identified the posterior wall of the bursae as the cortical vitreous. To avoid the older, unsupported connotations associated with the term premacular bursa, Kishi changed the name to posterior precortical vitreous pocket.…”
Section: Discussionmentioning
confidence: 95%
“…However, Kishi implied that the pocket was a nearly isolated contained structure that had specific dimensions, particularly vertically, that could be measured. 17 In 2003 Spaide, in a study using contact Bscan ultrasonography, found a hyporeflective cavity in the preretinal vitreous and interpreted this finding to represent the posterior precortical vitreous pocket. 20 The findings of the present study suggest the premacular bursae and its connections to interlinked spaces are too small to be accurately delineated by ultrasonography and the geometry is too complex to be accurately described by simple size measurements as performed by Kishi and associates 17 and by Stanga and associates.…”
Section: Discussionmentioning
confidence: 97%